Structural and electrical characterization of NaNbO 3 -PVDF nanocomposites fabricated using cold sintering synthesis route - Gyan D.S.; Dwivedi A. (My University, 2025)
Sodium niobate (NaNbO 3 ) powders and nanowires were synthesized and subsequently used for preparing composites with polyvinylidene-fluoride (PVDF) using the cold sintering technique in the weight ratio of 80:20 (ceramic:polymer). Phase purity of ceramic powders and nanowires was confirmed by X-ray diffraction analysis. Different phases of PVDF formed under various process parameters were also identified. Thermo-gravimetric analysis was performed in order to check the thermal stability of the composites. SEM was used to study the surface morphology of these samples, and energy dispersive x-ray analysis was also carried out in order to view the distribution of polymers in the composites. Furthermore, the formation of the ceramic matrix in the composites was verified and distribution of polymers in the ceramic matrix was examined by micro-computed tomographic analysis. Dielectric constant and loss tangent were measured and compared with the theoretically calculated values. Theoretical breakdown strength and energy density were calculated and were found to be as high as 1345 kV/cm and 6.1 J/cm 3 , respectively, at room temperature. Discharge efficiency of 64% was obtained for annealed nanocomposites. © 2018 Author(s).